How Does Climate Policy Uncertainty Affect Green Innovation Among Chinese Companies? - Chen, Aonan; Feng, Jingwen; Cheng, Yangyang (Sustainability, 2025)
Climate change is a major challenge for humanity, with important implications for corporate development. Based on the data of China’s A-share listed companies from 2000 to 2021, this study evaluates the impact of climate policy uncertainty (CPU) on firms’ green innovation using a two-way fixed-effects model. It is found that CPU inhibits firms’ green innovation by reducing government support and external investment, with corporate green innovation declining by 3.3% for each unit increase in CPU. The mechanism studies reveal that CPU has impeded corporate green innovation by reducing corporate social responsibility and increasing corporate financing constraints. The heterogeneity analyses indicate that the negative effect of CPU was more noticeable in state-owned enterprises (SOEs), heavily polluting firms, and firms with a high equity concentration. Further exploration of the economic consequences suggests that CPU has weakened enterprise market competitiveness, including market share, market value, and management efficiency. Climate policy uncertainty is an important external factor for sustainable development, and this paper discusses the impact of climate policy uncertainty on corporate green innovation, which can help to realize the coordinated development of climate policy and corporate green innovation.